An updated checklist for the pseudoscorpion fauna of Hungary (Arachnida: Pseudoscorpiones) - Novák, János (Zootaxa, 2024)
An updated checklist of the pseudoscorpion fauna of Hungary is presented. Chthonius cf. alpicola Beier, 1951 is newly reported for the country. Neobisium inaequale Chamberlin, 1930 is regarded as a junior synonym of N. sylvaticum (C.L. Koch, 1835) (syn. nov.). Chelifer tegulatus Tömösváry, 1883 is regarded as a junior synonym of Dactylochelifer latreillii (Leach, 1817) (syn. nov.). Rhacochelifer quadrimaculatus (Tömösváry, 1882) is regarded as a senior synonym of Beierochelifer peloponnesiacus (Beier, 1929) (syn. nov.), forming the combination Beierochelifer quadrimaculatus (Tömösváry, 1882) (comb. nov). Furthermore, Chthonius pygmaeus (Beier, 1934), Neobisium (Neobisium) simoni (L. Koch, 1873), Neobisium (Neobisium) validum (L. Koch, 1873), Rhacochelifer peculiaris (L. Koch, 1873), and Chernes montigenus (Simon, 1879) are excluded from the Hungarian fauna. Neobisium (N.) seminudum (Daday and Tömösváry, 1880) and Chelifer entzii Daday and Tömösváry, 1880 are designated as nomina dubia. As a consequence, the pseudoscorpion fauna of Hungary now comprises 49 species belonging to eight families with confirmed occurrence data; the occurrence of 6 further species recorded earlier for Hungary is doubtful. Phoresy is documented for Ephippiochthonius tetrachelatus (Preyssler, 1790) and Diplotemnus balcanicus (Redikorzev, 1928). Habitat preference of each species with confirmed occurrence in Hungary are assumed. Notes are given to some old data reported by Ödön Tömösváry and Eugen Daday from neighbouring countries. Microbisium manicatum (L. Koch, 1873) is excluded from the fauna list of Romania.